Determination of amoxicillin cross-contamination in Ibuprofen tablets using ultra performance liquid chromatography and IDEXX snap kit - Ali, Mohamed Ali Mohamed (2017)
Penicillin is one of the most effective β-lactam antibiotics against bacterial infections. Nevertheless, the allergic reactions associated with the usage of penicillin ranges from rashes to life-threatening anaphylaxis. Hence, the regulations imposed the pharmaceutical manufacturers to implement strict controls during the production process compels these manufacturers to test non-penicillin drug products for traces of penicillin in which the possibility of exposure to cross-contamination exists. Furthermore, the United States Food and Drug Administration (USFDA) prohibit the marketing of such products if detectable penicillin levels are found. In-depth investigations revealed a real need for an analytical technique, with appropriate detection level, that can determine the presence of penicillin in non-penicillin medicines. The intent of this study was to develop, optimize, and validate two analytical methods for determination of the amoxicillin as a β-lactam penicillin contaminant in ibuprofen tablets 400 mg using ultra performance liquid chromatography (UPLC) and Idexx SNAP® β-lactam test kits. In the first case, a novel quantitative analytical method was developed and validated using UPLC. Extraction of amoxicillin was done in double-distilled water, and separation of the different compounds wasachieved using a bridged ethylene hybrid (BEH) C18 column with a particle size of 1.7 μm (100 mm × 2.1 mm). The isocratic run was accomplished using phosphate buffer (pH=5.0): methanol (95:5, v/v) as mobile phase at a flow rate of 0.3 ml/min. The specificity and accuracy of the method proved to be suitable within the requirements of the current Good Manufacturing Practices (cGMP) for finished pharmaceuticals. The developed method was validated according to the International Conference on Harmonization (ICH) guidelines Q2 (R1). The method was linear in the range of 24 to 96 μg/l for amoxicillin with a correlation coefficient r = 0.999. The lowest detection limit of amoxicillin was found to be of 0.008 μg/ml. The recovery data was found to be in the range of 97.6% to 101.7%. The precision was assessed in terms of injection repeatability with the maximum relative standard deviation (RSD) of 1.8%. Highly reproducible results with RSD of 1.97% were obtained for a series of measurements of the analyte in two different days. Applying the developed UPLC method will enhance the approval process in the pharmaceutical industry significantly. In the second study, a qualitative screening method for determination of cross-contamination of amoxicillin in ibuprofen tablets 400mg using Idexx SNAP® β-lactam test kits was optimized and validated. The kit is one of the USFDA approved biosensors that is used for detection of β–lactam antibiotics in milk samples. It was established based on an enzyme-linked, receptor binding assay mechanism. The method was validated according to the European Commission Decision 2002/657/EC, and satisfactory results were obtained for its performance characteristics. Twenty (20) negative controls and 20 positive samples revealed that the method wasspecific with no false-compliant results. The detection limit (DL) of amoxicillin proved to be below the USFDA established a safe level of 10 parts per billion (ppb) with a total assay time of 10 minutes. In a variety of matrices, the method was applied to 13 different oral solid pharmaceutical products with a maximum negative reading of 0.88 and minimum positive reading of 1.31. The ruggedness of the method was confirmed through the design of experiment (DOE) approach in which 1/16 fractional factorial design was constructed using Minitab software to obtain maximum information from the least amount of experimental runs. In general, both of the UPLC and Idexx SNAP® screening methods were able to detect the amoxicillin in the ibuprofentablets at the safe level and can be applied successfully in pharmaceutical quality control laboratory to fulfill the regulatory requirements.